The Mixed Category of Human/Animal in Greimas’ Mythologies. Transl. by Ramunė Brundzaitė - Migliore, Tiziana (Semiotika, 2019)
Translated from Tiziana Migliore, „L’interspecie umano-animale nelle Mitologiche di Greimas“, in: Algirdas Julien Greimas, Mitologiche. La semiosfera lituana, a cura di Paolo Fabbri, Roma: Aracne editrice, 2007, p.187–195. Transl. by Ramunė Brundzaitė.
Keywords: Greimasean mythology; narrativity; zoosemiotics